Do insurers manipulate loss reserves to mask solvency problems? - Gaver, Jennifer J.; Paterson, Jeffrey S. (Journal of Accounting and Economics, 2004)
We report that insurance firms manage loss reserves to avoid violating certain test ratio bounds (known as IRIS ratios) that are used by regulators for solvency assessment. In our sample, almost two-thirds of the firms that would violate four or more IRIS ratios successfully adjust reserves to reduce the reported number of violations to less than four. This finding is significant because four violations usually trigger regulatory intervention. Our results indicate that non-earnings goals are an important influence on discretionary accounting choice. They also suggest that reserve manipulation can postpone needed regulatory intervention, sometimes for an extended period.